Application of Mandi Balimau Kasai Local Wisdom Values in History Learning to Improve Students' Religious Character - Afrilianti, Anggi; Miftahuddin, Miftahuddin; Bunari, Bunari; Suroyo, Suroyo; Soriente, Antonia (Universitas Negeri Malang, 2023)
This study aims to explore the impact of implementing Mandi Balimau Kasai local wisdom values in history education on the development of students' religious character. The research employs an experimental design with a pre-test and post-test one group design. The research subjects consist of 45 high school students in the Riau region. Data collection instruments in this study include questionnaires used to measure students' religious character. Data analysis methods involve both statistical analysis and descriptive analysis. Descriptive analysis is used to summarize students' religious character data before and after the treatment, providing a general overview of the changes in students' religious character. Statistical analysis includes paired t-tests and simple linear regression analysis. The results of the study indicate that students' religious character in the pre-test stage significantly influences their religious character in the post-test stage. A positive regression coefficient of 0.75 suggests that an increase in religious character in the pre-test stage is positively correlated with an increase in religious character in the post-test stage. Furthermore, an R-squared value of 0.74 indicates that approximately 74% of the variability in religious character in the post-test stage can be explained by students' religious character in the pre-test stage. This research provides valuable insights into the role of local wisdom values in enhancing students' religious character. However, there are limitations to the study, including the focus on Mandi Balimau Kasai as the sole local wisdom in Riau and the research subjects limited to high school students. Therefore, a recommendation for future research is to broaden the scope by examining the effectiveness of implementing other local wisdom values in a broader context. Additionally, other factors influencing students' religious character, such as the social environment, religious education, and family influences, need to be considered. The results of this study can be beneficial in developing more effective curriculum and teaching strategies to enhance students' holistic religious character development.